Description of Vacuolonema iberomarrocanum gen. et sp. nov. (Oculatellales, Cyanobacteria): a new marine cyanobacterial taxon from the Portuguese and Moroccan Atlantic coast - Morais, João; Hentschke, Guilherme Scotta; Oliveira, Flavio; Silva, Raquel; Leão, Pedro N.; Sabour, Brahim; Vasconcelos, Vitor (Phytotaxa, 2025)
Cyanobacteria biodiversity remains underexplored despite their ecological importance and potential applications. To address this, we investigated two Leptolyngbya-like strains, LEGE 07170 and LEGE 191244, collected from marine tide pools in Portugal and Morocco using polyphasic approach. Phylogenetic analyses indicates that the strains form a distinct clade with strong statistical support in the Oculatellales order. The 16S rRNA gene identity matrix shows that the maximum shared values with the phylogenetically closest genera Gansulinema, Kaiparowitsia, Shahulinema, Aerofilum and Thermoleptolyngbya is consistently below 94.5%. Morphologically, LEGE 07170 and LEGE 191244 are indistinguishable to each other. Both optical and TEM analyses showed vacuole-like structures at the cells cross-walls and this character morphologically distinguishes these strains from their phylogenetically related genera. The 16S–23S ITS secondary structures also differed the LEGE-CC strains from their closest related genera.